Hysteretic performance of stubby Y-type perfobond rib shear connectors depending on transverse rebar. (10th March 2019) - Kim, Kun-Soo; Han, Oneil; Choi, Jonghee; Kim, Sang-Hyo
Graphical abstract: Highlights: Hysteretic performance of stubby Y-type perfobond rib shear connectors was studied. Effect of the diameter for the transverse rebar was evaluated. Monotonic and cyclic loading tests were performed on different specimens. Energy dissipation capacity, shear strength, ductility increased with the diameter. Stiffness degradation was comparable for all diameters. Abstract: The shear behavior of stubby Y-type perfobond rib shear connectors differs according to the diameter of the transverse rebar used for composite action. Pull-push test specimens with transverse rebar of different diameters (D10, D13, D16) were manufactured for monotonic and cyclic loading tests to investigate the effects on not only the shear resistance but also the hysteretic performance. The energy dissipation capacity, shear strength, and ductility increased with the diameter of the transverse rebar, while the stiffness degradation appeared comparable. The specimens with D16 transverse rebar had high ductility, while those with D10 and D13 transverse rebar had moderate ductility.